Transplacental transferred anti-SARS-CoV-2 neutralizing antibodies in unvaccinated pregnant women in Cameroon occurred during the COVID-19 pandemic, but not in the pre-pandemic period - Seumko’o, Reine Medouen Ndeumou; Moyo-Gwete, Thandeka; Hermanus, Tandile; Tene, Sosthene Hillary Matabou; Djounda, Romeo Brice Dieffouo; Nana, Chris Marco Mbianda; Bitye, Bernard Marie Zambo; Zangue, Tekougang Berenice Kenfack; Tchakounte, Bodin Darcisse Kwanou; Ngolle, Eitel Mpoudi; Taylor, Diane Wallace; Leke, Rose Gana Fomban; et al. (Frontiers in Immunology, 2025)
IntroductionNeutralizing antibodies (NAbs) are critical for protection against SARS-CoV-2, but there is limited information on their role in pregnancy, especially among Cameroonian women. Here, we aimed to determine the prevalence of pan-coronavirus reactive antibodies from pregnant women sampled before and during the COVID-19 pandemic.MethodsPlasma samples from 629 women in the second trimester and 661 at delivery were collected pre-COVID-19 and from 39 women at delivery during COVID-19 in Yaoundé, Cameroon. All samples were screened using the Abbott Panbio™ COVID-19 rapid diagnostic test (RDT). Enzyme-linked immunosorbent assays (ELISA) and the spike-pseudotyped lentivirus neutralization assay were done to measure antibody binding and neutralizing capacity in 118 and 33 samples, respectively.ResultsBefore the pandemic, 16.5% (213/1290) of pregnant women were seropositive for cross-reactive anti-SARS-CoV-2 antibodies by RDT, while 12.2% (11/90) were seropositive to antibody binding by ELISA. Additionally, no correlation was found between cross-reactivity against the spike protein of SARS-CoV-2 and the HCoVs-OC43 and HcoVs-NL63 spikes. However, during the pandemic, 53.8% (21/39) of women sampled at delivery were seropositive by RDT, all women (28/28-100%) were seropositive by ELISA and 90% (20/22) of the samples from pregnant women tested for neutralization (20/22) had detectable neutralizing antibody responses during the COVID-19 pandemic. A transplacental transfer of binding antibodies from the mother to the child was found in 76.9% (30/39) of the tested dyads with a high prevalence during pandemic (26/28-86.7%) than prior the pandemic (4/11-13.3%).DiscussionThis study goes to reinforce the need for vaccination as though, all participants elicited a response towards endemic coronaviruses before the COVID-19 pandemic, a very small fraction of participants had binding antibodies which cross-react with SARS-CoV-2 and none of these were neutralizing. Anti-SARS-CoV-2 antibodies from the studied pregnant Cameroonian women at delivery during the pandemic had neutralizing activity against the founder variant and were efficiently transferred to the newborn. However the neutralization against other variants of concern warrants future investigation.